PENGARUH PENERAPAN SISTEM INFORMASI AKUNTANSI DIGITAL TERHADAP PENCEGAHAN FRAUD ACCOUNTING PADA PEMERINTAH DESA MASOSO - Irwan Pratama; Nur Asia; Mediaty; Rahmawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the influence of implementing a Digital Accounting Information System (AIS) on the prevention of accounting fraud in Masoso Village Government. The significant increase in village funds over the years poses a higher risk of financial manipulation and fraudulent accounting practices. To address these risks, the use of digital Accounting Information Systems is expected to enhance transparency, accuracy, auditability, and accountability of village financial management. This study employs a quantitative approach using 45 respondents involved in the administrative and financial management processes of Masoso Village. Data were collected via a validated Likert-scale questionnaire and analyzed using validity testing, reliability testing, normality testing, simple linear regression, t-test, and coefficient of determination (R²). The findings show that the digital AIS has a significant effect on fraud prevention, indicated by the t-value of 6.821 and significance level of 0.000. Additionally, the R² value of 0.595 implies that 59.5% of fraud prevention efforts are influenced by the implementation of digital AIS. The study concludes that increasing the quality of digital accounting system implementation can effectively reduce opportunities for fraud, strengthen internal control, and improve accountability in village financial governance